A stably enhanced transparent conductive graphene film obtained using an air-annealing method. (4th August 2016) - Song, Xuefen; Wei, Dapeng; Sun, Tai; Yu, Leyong; Yang, Jun; Zhang, Yongna; Fang, Liang; Wei, Dacheng; Shi, Haofei; Du, Chunlei
Abstract: A simple and effective air-annealing technique was developed to stably improve both the electrical conductivity and light transmission of pristine graphene. After the graphene film was annealed in air at 250 °C for 80 min, the mobility and carrier concentration were both significantly enhanced, and the sheet resistance was greatly reduced with a decrease rate of ∼33%. Meanwhile, the transparency was also improved by more than 3%. The mechanism is carefully discussed. The reason might be that air-annealing conditions provide a suitable atmosphere to etch and remove amorphous carbons. More importantly, the enhanced transparent conductive properties of the air-annealed graphene films were extraordinarily stable, and remained almost unchanged for 100 days.